Filipino College Students' Views on The Value of Phisical Appeal to Political Leadership - Labor, Jonalou S. (UI Scholars Hub, 2017)
Musings of thirty-six college students from three higher educational institutions in the Manila, Philippines were used to look at the constructs of physical appeal and its power to influence leadership. By thematically analyzing the musings of the students, the research found physical appeal concepts that are associated to leadership. The study revealed that the students perceive leadership in two ways: from “within” the leader such as skills and knowledge, and from the “outside” where leadership is associated to goals, to influences, and to authority. In terms of physical appeal, leaders are expected to possess physical beauty (kagandahanganyo). Moreover, leaders are seen as individuals who have good manners (kagandahang asal). Interestingly, the college students claimed that leadership should also be based on capacity (kakayanan) and connection (koneksyon). These findings revealed that leadership has its physical and ethical forms that help the students visualize their idealized national political leader.